Formulation And Evaluation Of Colon Targeted Oral Drug Delivery Systems For Metronidazole In Treatment Of Amoebiasis - BHAWNA GAURI; SHAILENDRA K SINGH; DIMPLE CHOPRA (International Journal of Pharma and Bio Sciences, 2011)
The aim of study is to develop colon targeted system for metronidazole using guar gum and xanthan gum. Matrix formulations containing various proportions of guar gum and xanthan gum were prepared by wet granulation technique. Later on, multilayer tablets were prepared by using 50 mg and 100 mg of guar gum as release controlling layer on either side of (M5) matrix tablets of metronidazole. The in-vitro drug release study was undertaken at 37±0.5°C in 0.1N HCl for 2 h; followed by pH 7.4 phosphate buffer (3h) finally in, simulated colonic fluid pH 6.8 phosphate buffer containing 4%w/v rat ceacal content for 15 h. Results indicated that guar gum was alone failed to control drug release. M5 (GG: XG, 0:100) formulation seemed to quiet promising for colonic drug delivery wherease, other matrices released 12-33% of metronidazole in physiological environment of GIT. When studies were continued in colonic fluids, matrix tablets released almost 100% drug. whereas, multilayer formulations did not release drug in stomach and small intestine, but delivered drug to the colon resulting in slow absorption of the drug and making drug available for local action in the colon.